Komunikasi Lingkungan Melalui Gerakan menanam seribu pohon di Kawasan Industri Desa Kecamatan Cibogo Kabupaten Subang - Nuraeni Nuraeni; Achmad Buchori; Dhina Khoerunisa (Universitas Garut, 2023)
The movement to plant a thousand trees is an initiative aimed at addressing climate change and raising awareness about the importance of environmental conservation. In this movement, the community is encouraged to actively participate in planting trees in various areas that need increased greenery. Environmental communication based on community participation plays a crucial role in this movement. Through media communication about planting a thousand trees, this movement has great potential to reduce carbon dioxide emissions, improve air quality, and protect biodiversity. Each tree that is planted contributes to carbon absorption, reduces greenhouse effects, and creates a cooler and more comfortable environment. In addition to the environmental benefits, the movement to plant a thousand trees also has positive social impacts. The goal of community involvement is to provide education and increase awareness of community participation in environmental preservation. The planting process involves community participation, strengthens social ties, and builds collective awareness of environmental protection. Furthermore, the growing trees provide long-term benefits such as increased natural resources like wood, fruit, and soil retention. The movement to plant a thousand trees serves as a platform to encourage action and change attitudes towards nature. By increasing the number of trees in our surroundings, we can create a greener, balanced, and sustainable environment for future generations. This initiative emphasizes the importance of cooperation, awareness, and shared responsibility in preserving and caring for nature as a valuable heritage for our future. The community engagement activities took place in Kampung Sukamulya Rt 14/04 and in the Cibeureum block of Cibogo village, Subang District, Subang Regency for 14 days, from January 13th to January 27th, 2023. Keywords: empowerment communication; community participation; tree planting movement.